2013
DOI: 10.1126/science.1239052
|View full text |Cite
|
Sign up to set email alerts
|

Topographic Representation of Numerosity in the Human Parietal Cortex

Abstract: Numerosity, the set size of a group of items, is processed by the association cortex, but certain aspects mirror the properties of primary senses. Sensory cortices contain topographic maps reflecting the structure of sensory organs. Are the cortical representation and processing of numerosity organized topographically, even though no sensory organ has a numerical structure? Using high-field functional magnetic resonance imaging (at a field strength of 7 teslas), we described neural populations tuned to small n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

59
551
2
6

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 446 publications
(618 citation statements)
references
References 65 publications
59
551
2
6
Order By: Relevance
“…Instead, the aIPS math sites were active only when subjects were required to interpret and manipulate numerals actively in the context of judging arithmetic statements. The aIPS math region we identify here is anatomically similar to the parietal regions in which previous studies have observed numerosity tuning in humans (24,71,72) and in macaques (4,73,74). However, although we are confident about the selective functional engagement of aIPS math sites during numerical processing, we are cognizant that future work is needed to disentangle further the functional roles of the aIPS math sites and nearby sites within different domains of numerical cognition.…”
Section: Numerical Processing In Discrete Neuronal Populations Withinmentioning
confidence: 67%
“…Instead, the aIPS math sites were active only when subjects were required to interpret and manipulate numerals actively in the context of judging arithmetic statements. The aIPS math region we identify here is anatomically similar to the parietal regions in which previous studies have observed numerosity tuning in humans (24,71,72) and in macaques (4,73,74). However, although we are confident about the selective functional engagement of aIPS math sites during numerical processing, we are cognizant that future work is needed to disentangle further the functional roles of the aIPS math sites and nearby sites within different domains of numerical cognition.…”
Section: Numerical Processing In Discrete Neuronal Populations Withinmentioning
confidence: 67%
“…6), reflecting common topographical organization across stimulus configurations and repeated measures. However, numerosity preferences from the configuration with constant-perimeter stimuli were consistently less well correlated with preferences from other stimulus configurations 2,13 . The numerosity maps for the left and right hemispheres represented different numerosity ranges.…”
mentioning
confidence: 90%
“…We distinguished between responses to numerosity and co-varying stimulus features using several stimulus configurations 2,16 . We summarized the fMRI responses using numerosity-selective population receptive field (pRF) models with two parameters: preferred numerosity and tuning width.…”
mentioning
confidence: 99%
“…However, the response to ipsilateral stimulation is often found to be weaker due to large amount of feedforward input stemming from lowerlevel visual neurons that only respond to stimulation in the contralateral field (Ffytche, Howseman, Edwards, Sandeman, & Zeki, 2000;Huk, Dougherty, & Heeger, 2002). One example of the functional consequences of cortical separation is the fact that adaptation to numerosity -believed to originate in parietal areas of the brain (Harvey, Klein, Petridou, & Dumoulin, 2013) -has been shown to transfer across visual space, but not visual hemifield (Burr & Ross, 2008;Choo & Franconeri, 2010). While parietal areas have relatively large receptive fields -as well as areas that do not show any form of retinotopic mapping -crossing into the opposite hemifield reduces the magnitude of the numerosity after-effect.…”
Section: Methodsmentioning
confidence: 99%